Institutional Pressures in IKPA Implementation at the Ministry of State Secretariat - Aryanto Aji; Desti Fitriani (Eduvest - Journal of Universal Studies, 2026)
This study offers a new perspective on the implementation of Budget Execution Performance Indicators (IKPA) at the Ministry of State Secretariat by applying institutional theory, specifically the concept of isomorphism and the strategic response framework, to analyze how organizational behavior is shaped by coercive, normative, and mimetic pressures. This study aims to examine the influence of these three pressures on the implementation of PER-5/PB/2024 and to identify strategic responses, behavioral dynamics, and obstacles faced in achieving performance targets. Using a qualitative case study approach, data were obtained through semi-structured interviews, observations, and analysis of documents and secondary data drawn from sources such as OM-SPAN and documents related to budget implementation. The results show a dominance of coercive pressures that encourage compliance, weak normative pressures, and limited internal mimetic pressures. Key challenges include uncertain activity schedules, weak internal coordination, uneven human resource capacity, and limited leadership commitment. These dynamics result in symbolic compliance and performance distortions that undermine the substantive validity of IKPA scores